Another Look at the Relationship between Cohabitation and Marriage – The Use of Crude and Net Probabilities. Issue 1 (October 2017) - Peristera, Paraskevi; Ghilagaber, Gebrenegus
In this paper we propose an approach based on the theoretical relationship between crude and net probabilities of marriage in a competing-risk framework. Analyses based on family dynamics among Swedish men born 1936-1964 show that the probabilities of marriage increase if cohabitation was eliminated (and that probabilities of cohabitation increase if marriage was eliminated). Further, the gains in net probabilities increase at the prime ages of family formation (20-28) but are less significant at other ages. Such results support (at least for the data at hand) the argument that informal cohabitation serves as a prelude to marriage rather than a permanent replacement to it.